A major practicum report at Sunpride Foods Incorporated S.E. Jayem St. Paknaan Mandaue City, Cebu - Layasan, Romena Sarah Naragas (2007)
As part of the curriculum of the Bachelor of Science in Food Technology, the student underwent a plant practice at Sunpride Foods Incorporated (SFI) in Paknaan, Mandaue City, Cebu from April 10 ? May 12, 2007. The trainee was given 288 hours to be exposed in different areas of the company. These areas include the quality assurance laboratory, production area, canning area, warehouse, research and development area. The objective of the plant practice is to gain experience in the operations involved in canned meat products like corned beef and other frozen processed products. During the practicum, the student encountered some minor problems in the existing operations as well as on the management of the food processing plant. The objectives of this manuscript include the documentation of the information gathered by the student and provision of suggestions to optimize the existing processing operations of the company